Changing Curriculum Practice in Early Childhood Education Setting: An Action Research to Enhance Authentic Assessment - Yunus, Faridah (Advances in Social Sciences Research Journal, 2017)
The goal of Early childhood education (ECE) is to provide environment to support children’s holistic development. Therefore, curriculum and assessment must be planned carefully to encourage activities that could nurture the development. This paper discusses the reflexive accounts of the author based on her experience, as an academician/researcher transforming an early childhood education practice in local context. The transformation from paper-and-pencil (P-P) activities/tests towards authentic curriculum and assessment practice was carried out as a democratic process guided by action research design. A catalyst in the form of Curriculum-Based Assessment (CBA) instrument was used to guide the author. There were four parts involved which are modification of (i) lesson plan, (ii) physical and social environment, (iii) children’s activities, (iv) assessment. These modifications were carried out throughout the one-year teacher training period. By applying reflexive technique to change the practice i.e. democratic approach, the training plans/syllabus had to be modified by alternating discussion with hands-on activities with the teachers. Data showed that changes in the physical settings and social atmosphere had led to a more responsive relationship between teachers and children. Hence, more criteria of development were nurtured than previously observed when children’s activities were focused on the P-P. These can be seen in the recorded photos, videos and work samples recorded in the children’s portfolio. Lack of academic qualifications and continuous trainings among the teachers posed a great challenge for the change to take place.